2015
DOI: 10.1007/s13762-015-0768-3
|View full text |Cite
|
Sign up to set email alerts
|

Statistical physical and nutrient optimization of bioplastic polyhydroxybutyrate production by Cupriavidus necator

Abstract: Polyhydroxyalkanoates are biodegradable polymer materials that accumulate in numerous bacteria. The polyhydroxybutyrate is the most common type of polyhydroxyalkanoates, which potentially serves as precursor for bioplastic production. The most extensively studied polyhydroxybutyrate producing bacteria is Cupriavidus necator due to its capability to accumulate large amounts of this biopolymer in simple culture medium. Accumulation of polyhydroxyalkanoates granules in the cytoplasm of C. necator significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…1). This indicates that the optimized combination of carbon and nitrogen sources at pH 6.8 and 200 rpm significantly increased biomass compared to that found by Aramvash et al (2015). They measured a biomass of 1.37 g/L from C. necator ATCC 17699 with 20 g/L glucose and 2.0 g/L (NH 4 ) 2 SO 4 at pH 7.0 after 48 h. The results revealed that this new mutant strain (C. necator NSDG-GG) in the present study is capable of increasing bio-transforming of glucose into biomass.…”
Section: Initial Culture and P(3hb) Productionmentioning
confidence: 63%
“…1). This indicates that the optimized combination of carbon and nitrogen sources at pH 6.8 and 200 rpm significantly increased biomass compared to that found by Aramvash et al (2015). They measured a biomass of 1.37 g/L from C. necator ATCC 17699 with 20 g/L glucose and 2.0 g/L (NH 4 ) 2 SO 4 at pH 7.0 after 48 h. The results revealed that this new mutant strain (C. necator NSDG-GG) in the present study is capable of increasing bio-transforming of glucose into biomass.…”
Section: Initial Culture and P(3hb) Productionmentioning
confidence: 63%
“…Inorganic chemicals such as ammonia, or ammonium salts are an important for maximizing biomass concentration and PHA accumulation [23]. Ammonium chloride was reported as the best nitrogen source for PHAs production by several researchers [17,[24][25][26]. Kalaiyezhini and Ramachandran [27] found that ammonium sulphate supported high growth and PHA production from glycerol in Paracoccus denitrificans.…”
Section: Discussionmentioning
confidence: 99%
“…However, agitation rates below the optimal level caused cell aggregation and a heterogeneous culture media (Musa et al, 2016). Furthermore, agitation was used as an optimisation parameter of PHA production in several studies (Aramvash et al, 2015;Geethu et al, 2019). Increasing the concentration of 1-pentanol from 0.03 to 0.09 wt% considerably increased the 3HV monomer composition, but the latter was unaffected by agitation or incubation time (Fig.…”
Section: Optimization Of P(3hb-co-3hv) Production Using the Statisticmentioning
confidence: 99%